Willingness of caregivers to have their daughters vaccinated against human papilloma virus and associated factors in Jimma Town, Southwest Ethiopia - Getachew, Anebo; Anand, Susan; Wodaynew, Tilahun (Frontiers in Global Women's Health, 2024)
IntroductionHuman Papillomavirus (HPV) is a widespread sexually transmitted infection and a leading cause of cervical cancer. Although there is a significant HPV prevalence in Ethiopia, yet the uptake of the HPV vaccine remains low. This study aimed to assess the level of caregivers' willingness to vaccinate their daughters against the human papilloma virus and associated factors in Jimma town.MethodsA community-based cross-sectional study was conducted from June 1–30, 2023. A total of 471 study participants were selected using multi-stage sampling techniques. Data was collected using an interviewer-administered questionnaire. Binary and multiple logistic regression analyses were done to identify associated factors, and the adjusted odds ratio and 95% confidence interval were computed. A value p of <0.05 was used to determine statistical significance.ResultsAbout 82.4% (95% CI: 79.0–86.0) of caregivers indicated a willingness to have their daughters vaccinated. Having college education or above (AOR:3.31, 95%CI:1.02–10.8), good knowledge of the HPV vaccine (AOR:2.25, 95%CI:1.05–4.85), good knowledge of sexually transmitted infections (STIs) (AOR:2.04, 95%CI: 1.09–3.82), good knowledge of cervical cancer (AOR:2.50, 95%CI:1.31–4.77) and a positive attitude towards the vaccine (AOR:4.03, 95%CI: 2.26–7.22), were associated with willingness.DiscussionThe majority of caregivers were willing to vaccinate their daughters against HPV. Caregivers who had higher education, good knowledge about the HPV vaccine, cervical cancer, and STIs, as well as positive attitudes towards the vaccine, were more likely to be willing to vaccinate. Efforts should be made to educate caregivers about the vaccine, cervical cancer, and STIs while promoting positive attitudes.